A Smart Greenhouse Production System Utilizes an IoT Technology - Choirul Huda; Bety Etikasari; Pramuditha Shinta Dewi Puspitasari (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2023)
Food is an essential need for every living creature. Choosing the wrong food leads to serious problems e.g. indigestion, obesity, diabetes mellitus, stroke, including heart disease that causes death. To prevent those diseases from harming the body, people should be concerned about food consumption, for example by consuming organic food. Organic food is obtained by cultivating plants in a greenhouse to increase production, minimize risk, prevent disease, and be safer against environmental risk. However, some obstacles faced by farmers such as disease or pests, water supply, temperature, and so on. Based on some previous research, the problem is dominated by soil moisture since the farmer has to water all plants manually. It has affected crop yields directly. If this phenomenon is not handled properly, farmers are threatened with losses so organic farming becomes a catastrophe. Therefore, in this research, an IoT technology is proposed to increase soil moisture in real time. The proposed system is also equipped with a Web-based information system to expose the cultivation phase, and market crops, as well as a tool for buyers as interaction media through the feedback provided. In the end, the proposed system is adequate to increase the productivity of vegetable cultivation grown in a greenhouse. Based on some experiments that have been done, the proposed method is capable to work optimally and effectively meet user needs by 95.55%.